Child Safe Browser Extension: A Browser Extension to Detect Adultery and Violent Content to Make Safer Web for Children - Alhossen, Md.; Himi, Rafika Zannat; Hasan, Zahid (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.